PENGARUH PROMOSI PENJUALAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI WORD OF MOUTH PADA MOBIL PAJERO SPORT DI KOTA PEKANBARU - Wahyu Rido; Restuti Sri; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Sales Promotion and Product Quality onPurchasing Decisions through Word Of Mouth on Pajero sports cars inPekanbaru City. The study was conducted on buyers of Pajero sports cars in thecity of Pekanbaru by distributing questionnaires to 100 respondents as samples.The sampling technique in this study used the Slovin formula with a 10%precision level. The data analysis method used is Path Analysis with the help ofSPSS application. The results showed that Sales Promotion and Product Qualityhad a significant effect on Word Of Mouth. then Sales Promotion, Product Qualityand Word Of Mouth have a significant effect on Purchasing Decisions. Salespromotion and Product Quality through Word of Mouth have a significant effecton Purchasing Decisions. Keywords: Sales Promotion, Product Quality, Word Of Mouth, PurchasingDecisions.